Pemanfaatan Speed Bump sebagai Pembangkit Listrik Energi Alternatif - Aris Suryadi; Emmanuel Agung Nugroho; Purwandito Tulus Asmoro (Prosiding Seminar Nasional Teknoka, 2019)
Speed bump or in Indonesian language called "Polisi Tidur", is considered less useful and disturbing for motorcyclists to reduce the speed of their motorbikes. An idea arose to design a device, which in its application could be utilized as a power plant with a generator driving sourced from a speed bump. By using a power electronics circuit as a regulator of the output produced. The research method of this tool is that when a vehicle passes a speed bump it will step on a bump that can move up and down, then the movement of the rise and fall of the bump is converted into a circular motion generator. The voltage generated from the generator is stored in the accumulator which will be used as electrical energy as needed. The purpose of this research is to be able to become a source of renewable alternative energy as a producer of electricity, to be able to utilize wasted energy into potential energy.